Female Silence and Psychotherapy through Feminist Approach in Alex Michaelides’s The Silent Patient - Al Areqih, Rashad (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study examines the roles of women in society and their attitudes toward family and societal expectations, focusing on Alicia and Theo Faber from Alex Michaelides's The Silent Patient (2019). It explores how Alicia's silence symbolizes the broader silencing of women by men and their search for meaning in chaos. Using a feminist lens, the study analyzes Alicia’s traumatic childhood, revealing how misogyny and patriarchal structures shape her life. It addresses key questions such as how her upbringing under a patriarchal system impacts her and how her perceived insanity becomes an escape from punishment. The study aligns with feminist critics who argue that Western narratives reflect masculine biases and perpetuate patriarchal values. The findings suggest that Alicia’s murder of her husband is a result of the compounded trauma of her childhood and the failure of her parents to protect her, ultimately leading to their tragic end. The study emphasizes the complex relationship between personal trauma and societal oppression, highlighting how these forces shape Alicia’s actions and fate.